2017
DOI: 10.1021/acs.energyfuels.6b03387
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Model of Single Particle Pulverized Coal Combustion Extended to Oxy-Coal Conditions

Abstract: Oxy-fired coal combustion is a promising potential carbon capture technology. Predictive CFD simulations are valuable tools in evaluating and deploying oxy-fuel and other carbon capture technologies either as retrofit technologies or for new construction. However, accurate predictive simulations require physically realistic submodels with low computational requirements. In particular, comprehensive char oxidation and gasification models have been developed that describe multiple reaction and diffusion processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Despite well-known weaknesses of the onestep heterogeneous model analysed here, it is commonly used in literature to give a quantitative description of different experimental or fuel-dependent parameters on the resulting reactivity, motivating its use in the experimental and numerical investigations here. However, a variety of other char combustion models exist, many of them consider more physical and chemical effects than the one-step kinetics model, which has been applied here (for example, the CBK model family [10,20], and Senneca's model [26], to name a few). Although different in their overall structures, these models all consider multiple chemical reactions for char conversion, coupled serially and/or in parallel.…”
Section: Resultsmentioning
confidence: 99%
“…Despite well-known weaknesses of the onestep heterogeneous model analysed here, it is commonly used in literature to give a quantitative description of different experimental or fuel-dependent parameters on the resulting reactivity, motivating its use in the experimental and numerical investigations here. However, a variety of other char combustion models exist, many of them consider more physical and chemical effects than the one-step kinetics model, which has been applied here (for example, the CBK model family [10,20], and Senneca's model [26], to name a few). Although different in their overall structures, these models all consider multiple chemical reactions for char conversion, coupled serially and/or in parallel.…”
Section: Resultsmentioning
confidence: 99%
“…Later, these sets of oxidation and gasification reactions were combined by Shurtz 41 in the Carbon Conversion Kinetics (CCK) model, which is also employed in the Carbon Conversion Kinetics for oxy-coal combustion code (CCK/oxy). 42 Liu and Niksa, 39 in particular, noted that their model could not match an extensive compilation of coal combustion rate data unless they allowed for a distinct activated complex for each primary gasification agent (i.e., one C(O) for O 2 , another for CO 2 , and another for H 2 O). Senneca et al 21 further observed that annealing appeared to decrease both the adsorption and desorption preexponential factors for char combustion.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…For example, Liu and Niksa , used five reaction steps for gasification and an additional three steps for O 2 char oxidation. Later, these sets of oxidation and gasification reactions were combined by Shurtz in the Carbon Conversion Kinetics (CCK) model, which is also employed in the Carbon Conversion Kinetics for oxy-coal combustion code (CCK/oxy) . Liu and Niksa, in particular, noted that their model could not match an extensive compilation of coal combustion rate data unless they allowed for a distinct activated complex for each primary gasification agent (i.e., one C­(O) for O 2 , another for CO 2 , and another for H 2 O).…”
Section: Literature Ideas Conclusion and Implicationsmentioning
confidence: 99%
“…The most advanced char conversion models available consider a limited degree of complexity in chemical kinetics. A more complex chemical description was formulated by Haynes and co-workers, , defining the concepts of turnover models for char oxidation, and explaining how surface reactions expose unreactive carbon to the gaseous environment. In this case the reactivity of different structures is described by means of a continuous distribution of activation energies.…”
Section: Introductionmentioning
confidence: 99%